Autonomia do paciente terminal: percepção da enfermagem de uma unidade de internação hemato oncológica - Cassol, Paulo Barrozo (2014)
This study aimed to understand the perception of the nursing staff regarding patient autonomy terminally ill. This is a survey of qualitative, descriptive and exploratory approach was made with twenty three professional nursing team (auxiliary nursing, nursing technicians and nurses Medical Clinic I), University Hospital, Federal University of Santa Maria. For the production of the semi driven data, recorded between September 2013 and October was used. The ethical dimension N. 466/2012 was respected according to the National Council of Health. After collection, the interviews were transcribed and analyzed by content analysis. Emerged from the interviews, four categories: transience of autonomy to heteronomy, communication of diagnosis, early policy of the will: uncertainties in its implementation; life support: the suffering of the inseparability patient care practices. We conclude that the terminal patient hospitalized at the Medical Clinic I have little autonomy over themselves, being owned by the medical decision-making power and especially the family. It is hoped that this research generates an improvement on the autonomy of the terminally ill patient, in order to generate ideas and actions in teaching and nursing.